Studies on Arylhydrazones, Part XVI: synthesis of Heterocyclic Compound from Diethylmesoxalate-o-Carboxyphenylhydrazone - Sahay, A.; Singh, N.P.; Singh, S.K. (Asian Journal of Chemistry, 2010)
The use of diethyImesoxaIate-o-carboxyphenyI-hydrazone (I) as a starting material for the synthesis of heterocyclic compound has been studied. Coupling proudct on fusion with NaOH at 130oC gives fully hydrolysed product. However fusion of compound (I) with NaOH at 220oC gives heterocyclic product. The fused products were characterised on the basis of elemental analysis, IR, 1H NMR and electron impact studies.